Consumer‐driven nutrient dynamics in freshwater ecosystems: from individuals to ecosystems. (23rd December 2016) - Atkinson, Carla L.; Capps, Krista A.; Rugenski, Amanda T.; Vanni, Michael J.
ABSTRACT: The role of animals in modulating nutrient cycling [hereafter, consumer‐driven nutrient dynamics (CND)] has been accepted as an important influence on both community structure and ecosystem function in aquatic systems. Yet there is great variability in the influence of CND across species and ecosystems, and the causes of this variation are not well understood. Here, we review and synthesize the mechanisms behind CND in fresh waters. We reviewed 131 articles on CND published between 1973 and 1 June 2015. The rate of new publications in CND has increased from 1.4 papers per year during 1973–2002 to 7.3 per year during 2003–2015. The majority of investigations are in North America with many concentrating on fish. More recent studies have focused on animal‐mediated nutrient excretion rates relative to nutrient demand and indirect impacts (e.g. decomposition). We identified several mechanisms that influence CND across levels of biological organization. Factors affecting the stoichiometric plasticity of consumers, including body size, feeding history and ontogeny, play an important role in determining the impact of individual consumers on nutrient dynamics and underlie the stoichiometry of CND across time and space. The abiotic characteristics of an ecosystem affect the net impact of consumers on ecosystem processes by influencing consumer metabolic processes (e.g. consumption and excretion/egestion rates), non‐CND supply of nutrients and ecosystem nutrient demand. Furthermore, the transformation and transport of elements by populations and communities of consumers also influences the flow of energy and nutrients across ecosystem boundaries. This review highlights that shifts in community composition or biomass of consumers and eco‐evolutionary underpinnings can have strong effects on the functional role of consumers in ecosystem processes, yet these are relatively unexplored aspects of CND. Future research should evaluate the value of using species traits and abiotic conditions to predict and understand the effects of consumers on ecosystem‐level nutrient dynamics across temporal and spatial scales. Moreover, new work in CND should strive to integrate knowledge from disparate fields of ecology and environmental science, such as physiology and ecosystem ecology, to develop a comprehensive and mechanistic understanding of the functional role of consumers. Comparative and experimental studies that develop testable hypotheses to challenge the current assumptions of CND, including consumer stoichiometric homeostasis, are needed to assess the significance of CND among species and across freshwater ecosystems.